Leadership and Transformative Change Management Relations in Nigeria: The Problems and Prospects - Nwele,; Obasi, James; Uruakpa,; Gospel, Chiagoziem (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
This study examines the impact of Chief executive officer’s leadership and transformative change management on organization and political societies. Societies and workplace grow more complex and the pace of change continues to accelerate and this lead to opportunities for innovative, confident leaders to make an impact through an organization’s or society’s most resilient resource which is its people or the workforce. It is a known fact that transformative leadership curbs bad attitude towards change. As a transformational development agent, the management of indices is complex. Just as it is no surprise that cynical attitude toward the prospect of change makes change harder to implement. Leaders are encouraged to inspire their employees and make them feel confident in their work as, with this, they have the best chance of limiting the development of such disabling attitude. Chief executive officers who engage in transformational leadership and change management should have a positive effect on organizational performance, or the society. In the hypothesis the author argued on 4 (four) contingencies that are particularly salient, which includes size or scope, status, tenure assessment, and value inclination of the society. That change management is concerned about a leader of change and his or her ability to recognize when change is needed and then get a crystal clear view of what is required to create the change supports the author’s argument on the hypothesis.